Research on the Application of Silver Nanowire-Based Non-Magnetic Transparent Heating Films in SERF Magnetometers - Yi Ge; Yuhan Li; Yang Li; Xuejing Liu; Xiangmei Dong; Xiumin Gao (Sensors)
We propose a non-magnetic transparent heating film based on silver nanowires (Ag-NWs) for application in spin-exchange relaxation-free (SERF) magnetic field measurement devices. To achieve ultra-high sensitivity in atomic magnetometers, the atoms within the alkali metal vapor cell must be maintained in a stable and uniform high-temperature environment. Ag-NWs, as a transparent conductive material with exceptional electrical conductivity, are well suited for this application. By employing high-frequency AC heating, we effectively minimize associated magnetic noise. The experimental results demonstrate that the proposed heating film, utilizing a surface heating method, can achieve temperatures exceeding 140 °C, which is sufficient to vaporize alkali metal atoms. The average magnetic flux coefficient of the heating film is 0.1143 nT/mA. Typically, as the current increases, a larger magnetic field is generated. When integrated with the heating system discussed in this paper, this characteristic can effectively mitigate low-frequency magnetic interference. In comparison with traditional flexible printed circuits (FPC), the Ag-NWs heating film exhibits a more uniform temperature distribution. This magnetically transparent heating film, leveraging Ag-NWs, enhances atomic magnetometry and presents opportunities for use in chip-level gyroscopes, atomic clocks, and various other atomic devices.